Vehicular delay tolerant network routing algorithm based on optimized multi-period Bayesian network - Jiagao WU; Yahang GUO; Shenlei CAI; Linfeng LIU (Tongxin xuebao)
Aiming at the instability of communication link caused by the high-speed movement of vehicle nodes in vehicular delay tolerant network （VDTN）， considering the characteristics of regularity and periodicity of vehicle nodes movement， a VDTN routing algorithm based on optimized multi-period Bayesian network （BN） was proposed.Firstly， a new multi-period BN model and its dynamic reward mechanism for node classification were proposed to describe the movement pattern of vehicle nodes with higher accuracy.Then， two novel time-optimal-partition algorithms of multi-period BN were proposed including binary search K2GA （BS-K2GA） algorithm and simulated annealing K2GA （SA-K2GA） algorithm， where BS-K2GA algorithm had the advantages of simplicity and efficiency， while SA-K2GA could effectively avoid falling into the local optimal solution and further optimize the performance.The simulation results show that the proposed VDTN routing algorithm based on optimized multi-period BN model can significantly improve the message delivery ratio and reduce the delivery delay.Thus， the effectiveness of the approach is validated.